(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Fatusene village is a mountainous area that has potential for oyster mushroom cultivation. the group of women farmers are housewives who have free time apart from weaving and serving their husbands and children. This service activity aims to improve farmers’ abilities in transforming agricultural production in the form of oyster mushrooms based on innovative technology, but partner communities do not yet have an understanding of mushroom cultivation literacy, so mentoring and training activities need to be carried out in empowering partner communities to cultivate oyster mushrooms with technological support. innovative. the method used is the counseling and mentoring method. the implementation time is September-November 2023. The output produced is mushroom products, increasing the skills of partners in cultivating oyster mushrooms.